Pertanggungjawaban Pidana Terhadap Pelaku Usaha Penimbun Minyak Goreng Bersubsidi - Mega Sofia Tawainella; Hadibah Zachra Wadjo; Judy Marria Saimima (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Currently, most cooking oil in circulation tends to be pegged at the old price or above the Highest Retail Price (HET) set by the government some time ago.Purposes of the Research: This research aims to analyze and explain criminal liability for business actors who hoard subsidized cooking oil. Analyze and explain supervision and law enforcement for business actors who hoard subsidized cooking oil. Methods of the Research: The type of research used is normative, namely research that focuses on providing a systematic explanation that regulates a certain category. The problem approaches are the statutory approach and the conceptual approach. Collecting legal materials through primary legal materials is then linked to secondary legal materials. Management and analysis of legal materials are described qualitatively.Results of the Research: Entrepreneurs in the business of hoarding subsidized cooking oil can be held criminally liable, namely in the form of imprisonment, compensation for fines or revocation of business permits. Regarding supervision and law enforcement for business actors hoarding cooking oil, it is still felt to be inadequate because law enforcement's understanding of the hoarded cooking oil commodity is whether it is a prohibited commodity or carries a criminal penalty if hoarding occurs and feels this is a problem for the Ministry of Trade and regional governments. The author would like to add that there is no criminal liability for the case of hoarding cooking oil because what is being processed is not a corruption crime at the Ministry of Trade involving entrepreneurs and the Director General of the Ministry of Trade.